Arabic translation and cross-cultural adaptation of Sport Concussion Assessment Tool 5 (SCAT5) - Holtzhausen, Louis J.; Souissi, Sofiane; Al Sayrafi, Omar; May, Awartani; Farooq, Abdulaziz; Grant, Catharina C.; Korakakis, Vasileios; Rabia, Safia; Segers, Souhaila; Chamari, Karim (Biology of Sport, 2021)
The aim was to create a Modern Standard Arabic SCAT5 version for different Arabic dialects. This translation and cross-cultural adaptation was performed in eight stages: initial translations, reconciliation of translations and cultural adaptation, back translation, appraisal of back translations, validation of the translation, review and adjustment by reconciliation committee, pretesting in 12 football players and document finalisation. As an alternative to the problematic Months In Reverse Order Test (MIROT) in Arabic, the Serial 3s test (32 Arabic and 30 English participants), the Days of the Week Backwards test (DWBT), and the ‘Adding Serial 3s’ test were tested (30 English and 30 Arabic participants) for accuracy, difficulty and time of completion. The Arabic SCAT5 was similar and comparable to the original English version (7-point Likert scales =< 2). Testing of the pre- final version of the Arabic SCAT5 took 20.4 (SD 3.4) and 17.7 (SD 3.0) minutes respectively to complete and was found acceptable in terms of clarity, understandability, grammatical correctness and coherence. The Arabic Serial 3s test (subtraction version) was unsuitable due to high completion time, low pass rate and high difficulty perception [time = 47.2 (SD 28.0) s; accuracy = 55.2%; difficulty = 3.2 (SD 1.1)]. The Arabic DWBT was too fast and undemanding for concentration testing [time = 4.6 (SD 1.5) s; accuracy = 90%; difficulty = 1.1 (SD 0.3)]. The Adding Serial 3s tests produced similar completion times [18.4 (SD 6.8) vs. 21.1 (SD 5.3), p = 0.088], accuracy (100%) and self-rated difficulty [English = 2.0 (SD 0.7) vs. Arabic-speaking participants = 2.1 (SD 0.8), p = 0.512] and was therefore adopted to replace the MIROT. This culturally adapted Arabic-SCAT5 questionnaire is the first concussion assessment tool available for Arabic-speaking healthcare providers and athletes.